Model produksi massal parasitoid Anagyrus lopezi (De Santis) (Hymenoptera: Encyrtidae) menggunakan kutu putih Phenacoccus manihoti Matile-Ferrero di laboratorium: Mass production model of the parasitoid Anagyrus lopezi (De Santis) (Hymenoptera: Encyrtidae) using the mealybug Phenacoccus manihoti Matile-Ferrero in the laboratory - Wasik, Muhammad Alimun; Dewi Sartiami; Ali Nurmansyah (Perhimpunan Entomologi Indonesia, 2025)
Anagyrus lopezi (De Santis) (Hymenoptera: Encyrtidae) is a specific parasitoid that plays an important role in the biological control of the cassava mealybug Phenacoccus manihoti Matile-Ferrero (Hemiptera: Pseudococcidae). Successful large-scale biological control requires the availability of this parasitoid in sufficient quantities through optimal and efficient mass production. This study aims to develop a mass production model for A. lopezi, taking into account mass rearing methods and the economic aspects of mass production. The experiment consisted of four treatments, namely 3, 6, 9, and 12 cassava cuttings of Manggu variety aged 2 weeks per cage measuring 75 cm × 50 cm × 50 cm. Each cutting was infested with 120 third-instar P. manihoti nymphs and four 2-day-old female A. lopezi obtained from laboratory rearing. Increasing the number of cuttings had a significant effect on the number of mummies produced, with the highest production achieved in the 9-cutting treatment (742.2 ± 12.21 mealybug mummies). The sex ratio of parasitoid progeny (1:2.21) was dominated by females, accounting for 68.91%. The production cost estimation included tools, materials, and labor wages. The total production cost per cage was IDR 48,425, with a cost per mummy of IDR 65. These findings provide technical and economic foundations for developing efficient and sustainable mass production systems of A. lopezi to support P. manihoti biological control programs in cassava plantations.